IMPROVING AND ACCELERATING DECISION-MAKING PROCESSES : A CASE STUDY IN AN MULTINATIONAL IT COMPANY - Sayyadi, Mahdi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
Interest in studying the speed of decision-making grew after it was argued that there was a positive relation between fast decision-making and better performance of firms. It was also proved that in high-velocity environments, firms that made faster strategic decisions achieved higher performance. The purpose of this study is to investigate decision-making processes in the case company in order to identify major impediments to fast and high-quality decision-making. This thesis also studies the underlying determinants to both quality and speed of decision-making processes in organizations and then identifies factors contributing to the acceleration and improvement of decision-making in the case company. The case company is a multinational telecommunication and IT company with nearly 100,000 employees around the world. In the first stage of this research, a critical literature review was conducted and literature was analyzed to identify major factors influencing the quality and speed of decision-making processes in organizations. In the second stage, a survey consisting of 16 questions was sent to 245 senior managers and strategic decision-makers in the case company to evaluate decision-making processes and shed light on the hindrances to both high-quality and speedy decision-making. After identifying both efficiencies and inefficiencies of decision-making in the case company, the results were analyzed and synthesized and then 22 proposals were developed to transform and strengthen decision-making processes in the case company. The findings and proposals were considered excellent results by the case company and led to organization-wide decision-making transformation. The findings of this study could be used by the companies that are willing to transform their decision-making processes to achieve high-quality and speedy decisions.